FORMULASI MULTISENSORY DALAM PEMBELAJARAN TEMATIK - Mohamad Maulidin Alif Utama (STAI Asy-Syukriyyah, 2020)
Learning materials that are still abstract is one of the obstacles for teachers in understanding students. Specific thematic learning, it is necessary learning that not only keeps students active in learning activities, but also students can understand the intent and purpose of the theme they are learning, the students' understanding can be improved through the model Multisensory learning.Multisensory learning is basically a learning that involves a variety of sensory stimuli including hearing, sight, touch, and sometimes also smell and taste. Multisensory learning models involve a variety of visual aids including IT-based media in support of its application process. The use of visual images, interactive video that is broadcast through the projector can certainly stimulate the student's sensory to the material being studied. Multisensory learning in practice is a learning that for learning materials that are abstract into concrete material. Therefore, the application of multisensory learning needs to involve a variety of critical inquiry activities conducted by students on the various realities of everyday life. for example, when teaching science on food chains, this material will be more easily understood by the child if the child is invited to directly watch the process of occurrence of the food chain in everyday life or at least watch the video showing the concept of the chain of food.The linkage between the multisensory learning model and the thematic learning lies in the process of implementation. The combination of sensory devices in multisensory learning is appropriate when applied to thematic learning in recognizing the material attributed to real-life everyday. Thematic learning uses many teaching aids and sometimes uses the senses that students have.